GREEN INTELLECTUAL CAPITAL AND RICH DIGITAL ECO-DYNAMIC TO IMPROVE E-BUSINESS SMES’ INNOVATION PERFORMANCE - Yuniarty Yuniarty; Ridho Bramulya Ikhsan; Hartiwi Prabowo; Juliater Simarmata (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research investigates the impact of green intellectual capital, dynamic capability, IT ambidexterity, environmental uncertainty, and RICH on the innovation performance of entrepreneurial small and medium-sized enterprises (SMEs). Focusing on Indonesian e-business SMEs, this study aims to deepen comprehension of the elements fostering innovation within SME entrepreneurship. Data were gathered from 313 SME entrepreneurs via online questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The study identifies key determinants influencing the improvement of innovation performance among Indonesian ebusiness SMEs and offers recommendations for its enhancement. Findings indicate that IT ambidexterity, environmental uncertainty, RICH, and green intellectual capital exert a significant positive effect on dynamic capability. Furthermore, dynamic capability, IT ambidexterity, environmental uncertainty, RICH, and green intellectual capital all demonstrate a substantial positive influence on innovation performance, with green intellectual capital emerging as the most impactful contributor. Ultimately, these insights can empower businesses to develop novel products and implement innovative marketing strategies, thereby expanding their market reach and customer base.